Identification of Expression Patterns and Potential Prognostic Significance of m5C-Related Regulators in Head and Neck Squamous Cell Carcinoma - Han, Zhenyuan; Yang, Biao; Wang, Yu; Zeng, Xiuxia; Tian, Zhen (Frontiers in Oncology, 2021)
N5-Methylcytosine (m5C) modification is a major epigenetic modification of RNAs and is dynamically mediated by m5C ‘writers’, ‘erasers’, and ‘readers’. RNA m5C modification and its regulators are implicated in the onset and development of many tumors, but their roles in head and neck squamous cell carcinoma (HNSCC) have not yet been completely elucidated. Here, we examined expression patterns of core m5C regulators in the publicly available HNSCC cohort via bioinformatic methods. The differentially expressed m5C regulators could divide the HNSCC cohort into four subgroups with distinct prognostic characteristics. Furthermore, a three-gene expression signature model comprised of NSUN5, DNMT1, and DNMT3A was established to identify high and low risks of HNSCC individuals. To explore the underlying mechanism towards the prognosis of HNSCC, differentially expressed genes among high- and low-risk HNSCC were screened, followed by the analysis of functional and pathway enrichment. Our results reveal a critical role for RNA m5C modification in two aspects of HNSCC: (1) dynamic m5C modification contributes to the regulation of HNSCC progression; (2) expression patterns of NSUN5, DNMT1, and DNMT3A help to predict the prognosis of HNSCC.